2015
DOI: 10.17577/ijertv4is030179
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review on Biomedical Waste and Effect of Mismanagement

Abstract: Biomedical waste is identified under many terminologies like hospital waste, healthcare waste etc., which are generated due to long or short term care of persons. Various health care establishments are the minor and major source of these types of wastes. Biomedical waste may be primarily classified as Hazardous and Non Hazardous wastes. Further, the biomedical waste is categorized by WHO and also under The Biomedical Waste (Management & Handling) Rules, 1998, India. According to previous studies the quantum of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(15 reference statements)
1
3
2
Order By: Relevance
“…Moreover, assessment of the result also shows that primary healthcare workers are not practicing proper biomedical waste segregation; only 28.0% of the respondents are practicing biomedical waste segregation out of 100% of total respondents which is against the biomedical waste management and handling rules. Poor or partial segregation is another problem associated with waste in the study area, a similar finding to [6] from Sokoto state, Nigeria. It is a trend that mixed the various types of wastes, and in turn lead to poor safety and management.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Moreover, assessment of the result also shows that primary healthcare workers are not practicing proper biomedical waste segregation; only 28.0% of the respondents are practicing biomedical waste segregation out of 100% of total respondents which is against the biomedical waste management and handling rules. Poor or partial segregation is another problem associated with waste in the study area, a similar finding to [6] from Sokoto state, Nigeria. It is a trend that mixed the various types of wastes, and in turn lead to poor safety and management.…”
Section: Discussionsupporting
confidence: 79%
“…[1], reported that the participants do not have zero awareness pertaining the amount and how much waste made in the different health locations (140%) out of 157 agreed that they do not label the infectious waste with the biohazard symbol. Lack of knowledge of infectious waste among staff, and other sanitary staff, cannot be absolved from been behind this trend [6]. However, some findings of this study, have shown a greater training on biomedical waste management among staff, which is a good omen and in contrast to a study by [6] from Sokoto.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…The harmful effects of these waste adversely affect the soil, ground-water and environment disbalancing the whole ecosystem. It include hospitals solid waste (80-90% toxic) which is highly infectious waste (Himabindu et al 2015). Also, when the world is fighting against COVID-19 pandemic, handling of waste is a serious issue that need to be improved.…”
Section: Cloud Computingmentioning
confidence: 99%